Construction of operational definitions in Metacognition - Peixoto, Mauricio Abreu Pinto (2021)
Since the 1970s metacognition has been understood as "knowledge and cognition about cognitive phenomena". Nevertheless its conceptualization, remains non-specific, most of the researchers neglecting the establishment of accurate metacognitive definitions. Thus, an intentional biased narrative review was carried out to construct operational definitions applicable on learning processes, enabling description and  discrimination between different metacognitive phenomena, and its classification and meaning attribution. The taxonomy presented here consists of 03 domains (Metacognitive Skills, Experience and Knowledge), containing 36 operational definitions of metacognitive terms.